La creazione mediatica della paura: lo spettro della censura tra cancel culture e politicamente corretto - Maddalena Cannito; Eugenia Mercuri; Francesca Tomatis (Cambio)
The article examines how Italian news coverage on Facebook has influenced the debate on cancel culture, linking it to phenomena like political correctness and framing it as an assault on freedom of expression. By analysing posts from 2020 to 2021 on the Facebook pages of major Italian newspapers, sourced through the CrowdTangle platform, the article explores the journalistic portrayal of cancel culture. It also considers how this media depiction has fostered an atmosphere of fear in a society where anxiety and unease, intensified by media representation, lose their tangible essence yet become increasingly pervasive. The thematic analysis identified two primary dimensions within the Italian journalistic discourse: the nature of cancel culture’s targets (people/objects) and their temporal context (present/past). The results indicate that contemporary journalism constructs the notion of a “cancel culture”, associating it with topics such as censorship, potential identity erosion, and the reinterpretation or denial of cultural and historical facets. This portrayal, intensified by the media, influences public perception and gives rise to growing feelings of unease and tension, culminating in a general climate of fear.